MIXER PENGADUK ADONAN UNTUK PENGRAJINSENI FIBERGLASS - Subiyono, Slamet Karyono, (Universitas Negeri Yogyakarta, 2011)
tProduction tools used by the craftsmen at Prambanan Yogyakartafiberglass is still very simple. There are 2 main tools used by the craftsmenwhich led directly influence both the quantity and quality of handicraftproducts. For mixing dough fiberglass, the craftsmen using improvised toolsand for finishing the painting, the craftsmen using hand brushes. From boththese tools, fiberglass dough mixer was chosen to be developed.The mixer uses elliptic vertical stirrer model with a larger radius atthe bottom. The purpose of this design is for rotating the flow of fluidinsideand sideway of the stirrer rotation and outside flow at the other area.The form of this mixer is a solution of the goal to produce a homogeneousmixture of fiberglass. Swivel stand is the stand of plastic bucket that will befilled with fiberglass dough. This bucket rotates automatically when themixing takes place. Thus an accelerated stirring and mixing a homogeneousmixture.Power uses¼ HPelectric motor with 1425 rpm. Motor speed is thenreduced by half through the pulley transmission. Mixer machineperformance is then compared between the old machines with new machinesassociated with the design of mixer and a different holder. Old mixer usinga single L shape stirrer rod, a new mixer using a mixer with a double ellipticshape intersect. Old mixer using the fix stand, while the new mixer using aswivel stand. Both productiveness of the mixer then compared in terms ofquantity and quality of mixing. Tests on the preparation of the second mixermachine does not show a significant difference, on average it takes 5minutes before stirring preparation done. Tests at the time of stirringshowed that the new mixer can mix faster than the old mixer. New mixerstirring just 5 minutes to produce a homogeneous mixture, while the oldmixer takes 10 minutes. Tests showed that the volume of new mixer capableof stirring the batter with a capacity of 4 times greater at around 20 liters,the results of this dough is much better visually and homogeneous. Theimplication of this finding is new mixer can improve the quantity andquality of fiberglass dough, and can be used as a substitute for the old mixerused byfiberglass industry targets.